Respuesta :
we know that
the formula of the the sum of the arithmetic sequence is
Sum=n*(a1+an)/2
n=36
a1=3
a36=?
find a36
an=a1+(n-1)*d
for n=2 a2=9
9=3+(2-1)*d----> 9=3+d----> d=6
so
for n=36
a36=a1+(36-1)*6----> a36=3+35*6----> a36=213
Sum=n*(a1+an)/2-----> 36*[3+213]/2----> 3888
the answer is
3888
the formula of the the sum of the arithmetic sequence is
Sum=n*(a1+an)/2
n=36
a1=3
a36=?
find a36
an=a1+(n-1)*d
for n=2 a2=9
9=3+(2-1)*d----> 9=3+d----> d=6
so
for n=36
a36=a1+(36-1)*6----> a36=3+35*6----> a36=213
Sum=n*(a1+an)/2-----> 36*[3+213]/2----> 3888
the answer is
3888